(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Examining the many cyber fraud methods, this research also examines their monetary, social, and psychological impacts, as well as the effectiveness of regulatory and legal responses to this problem. Methods such as theoretical analysis, empirical research, and case studies are used to achieve this goal. Not only that, it delves into the manner in which encryption, authentication, intrusion detection systems, AI, and ML combat cyber fraud and discovers proactive approaches to enhance cybersecurity resilience. By increasing understanding of cyber fraud and offering solutions based on evidence to prevent and react to it, this initiative aims to contribute to better cybersecurity in an increasingly interconnected and vulnerable digital world.